Fault-Tolerant Control of Four-Wheel Independently Actuated Electric Vehicles with Active Steering Systems★. Issue 21 (2015) - Jing, Hui; Wang, Rongrong; Chadli, Mohammed; Hu, Chuan; Yan, Fengjun; Li, Cong
Abstract: This paper presents a fault-tolerant control (FTC) strategy to improve lateral stability and maneuverability of a four-wheel independently actuated (FWIA) electric ground vehicle with active front steering (AFS). Front wheel steering angle and external yaw moment generated by the tire force difference between the two sides of the motors are adopted to simultaneously regulate the vehicle yaw rate and slip angle. Considering the high cost of currently available sensors for vehicle slip angle measurement, a robust H∞ dynamic output-feedback controller is designed to control the vehicle, which can be implemented without the slip angle or lateral speed measurement. Both vehicle parameter uncertainties and actuators faults are considered, making the proposed control method robust to the uncertainties and actuator faults. Simulation results based on full-vehicle model in Carsim validate the effectiveness of the proposed control approach.